LEARNING FOREIGN LANGUAGES AS A FASHION AND ANECESSITY FORTHE LABOUR MARKET - Umida Kurbanova Shuxratovna (Journals Park Publishing, 2023)
The relevance of the chosen topic is based on the need to develop foreign language learning in schools, children's schoolsand universities. It is precisely through foreign languages that international relations between the countries are developing.
Keywords: language, foreign language, people, youth, development, economy, parents, state, work, English, German, Spanish, certificates, negotiations, globalization, company, young, generation.